X-ray studies of the transformation from high- to low-density amorphous water. (3rd June 2019) - Mariedahl, Daniel; Perakis, Fivos; Späh, Alexander; Pathak, Harshad; Kim, Kyung Hwan; Benmore, Chris; Nilsson, Anders; Amann-Winkel, Katrin
Abstract : Here we report about the structural evolution during the conversion from high-density amorphous ices at ambient pressure to the low-density state. Using high-energy X-ray diffraction, we have monitored the transformation by following in reciprocal space the structure factor SOO ( Q ) and derived in real space the pair distribution function gOO ( r ). Heating equilibrated high-density amorphous ice (eHDA) at a fast rate (4 K min –1 ), the transition to the low-density form occurs very rapidly, while domains of both high- and low-density coexist. On the other hand, the transition in the case of unannealed HDA (uHDA) and very-high-density amorphous ice is more complex and of continuous nature. The direct comparison of eHDA and uHDA indicates that the molecular structure of uHDA contains a larger amount of tetrahedral motives. The different crystallization behaviour of the derived low-density amorphous states is interpreted as emanating from increased tetrahedral coordination present in uHDA. This article is part of the theme issue 'The physics and chemistry of ice: scaffolding across scales, from the viability of life to the formation of planets'.